Profile of Students' Reasoning Levels Using Ranking Task Exercises in Physics Learning - St. Syamsudduha; Fitriani Fitriani; Suhardiman Suhardiman (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
This research aimed to find out the reasoning level profile of students by using Ranking Task Exercise questions in the physics learning material for Work and Energy for class X MIPA at SMAN 24 Bone. The dependent variable in this study is the level of students' reasoning with this type of quantitative descriptive research. The subjects of this study were students of class X MIPA SMAN 24 Bone, totaling 49 people. The research instrument used was a question in a Ranking Task Exercise of ten numbers. Based on the research results, students' most common level of reasoning is the second level of reasoning category, namely subfunctional as many as 24 people with a percentage of 49%. The cause of the reasoning level of most students in the subfunctional category is that students still feel unfamiliar with questions in the form of the Ranking Task Exercise, so they have difficulty answering questions. In addition, the distance between giving material and giving questions is far enough that students have forgotten the concept of Work and Energy material. From this study, it can be concluded that the level of reasoning of students is still low. The order of the students' reasoning starts from the most to the least, namely sub-functional, unstructured/alternative, near functional, functional, and expert. This research implies that after the results of this research are obtained, it can be said that by knowing the level profile of students' reasoning in learning physics, it is expected to be an evaluation material for educators to apply an approach that can train students' scientific reasoning in learning physics.